Spatial and temporal genomic homogeneity among Haemophilus influenzae serotype f - Gonzalez-Diaz, Aida (2020)
Background: Haemophilus influenzae is an opportunistic pathogen highly adapted to the human respiratory tract which is often reported as the etiologic agent of infectious diseases. After the introduction of serotype b vaccine, non-typeable H. influenzae (NTHi) has become the most frequent cause of respiratory infection, followed in frequency by serotype f strains (Hif). The aim of this study was to analyze the genomic diversity among invasive and colonizing Hif isolates by whole genome sequencing (WGS).